2021
DOI: 10.48175/ijarsct-1050
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Staggered Truss System With and Without Shear Wall

Abstract: A staggered Truss System (STS) is a prospective steel structure system for high-rise buildings and a steel staggered truss framing system is one of the effective design techniques to improve the efficiency in building construction. Besides, cost reductions arise from a reduction in steel tonnage. The purpose of this study is to carry out a comparative analysis of staggered truss systems with and without a shear wall for 8, 9, and 10-storey buildings using the ETAB software. In this analysis, time histories are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Zhou et al [ 22 ] indicated that with an increase in the open-web panel length of the truss, the top lateral displacement and ductility of the structure increase. Mistry et al [ 23 ] studied staggered truss systems with and without a shear wall by using ETAB software. The results showed that the staggered truss system with a shear wall is more efficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al [ 22 ] indicated that with an increase in the open-web panel length of the truss, the top lateral displacement and ductility of the structure increase. Mistry et al [ 23 ] studied staggered truss systems with and without a shear wall by using ETAB software. The results showed that the staggered truss system with a shear wall is more efficient.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the substitution of rotational friction dampers at the location of the plastic hinges can enhance ductility and reduce failure probability Zhou et al [22] indicated that with an increase in the open-web panel length of the truss the top lateral displacement and ductility of the structure increase. Mistry et al [23] studied staggered truss systems with and without a shear wall by using ETAB software The results showed that the staggered truss system with a shear wall is more efficient. It is not effective to enhance or improve the seismic performance of an ordinary staggered However, in a high earthquake intensity area, an ordinary staggered truss steel framing system may face the problem of insufficient ductility and energy dissipation capacity [17].…”
Section: Introductionmentioning
confidence: 99%